Information and Material Coordination for Projects Understanding and Improving the Supply Chain Management for Prototype Production in an Electronics Company - Brännhult, Oscar; Hanson, Fredrik (My University, 2019)
Veoneer is an automotive safety development company with development and production spread over 13 countries. The operations in Sweden consists of a production plant in Vårgårda and four engineering plants located in Linköping, Gothenburg, Stockholm and Skellefteå. The plant in Vårgårda is mainly focused on serial production but also responsible for manufacturing prototypes that are in the middle or late stages of development. As most of the prototypes are produced on serial production lines, tight coordination between project members, that are responsible for the prototypes, and the serial production team is necessary in order to have efficient and functioning operations. Due to capacity constraints and conflicts of interest between serial- and prototype production, it is important to utilize the time given from serial production in order for Veoneer to supply for the demand for prototypes. Thereby, preparations prior to production runs are essential to prevent the production lines from standing due to lack of material or information. The purpose of this thesis was thus to understand, map and document the information and material flow for prototypes at Veoneer’s production plant in Vårgårda, and further develop improvements related to the prototype supply chain management. To fulfill the purpose, empirical data of the current situation at Veoneer was collected by observing processes, interviewing people and measurement studies. In order to understand the process flow, a value stream map was constructed together with a process overview. The empirical data was then analyzed to identify problem areas related to the supply chain management for prototypes. The problem area created a basis for which the improvement suggestions and implementations were built upon. The suggestions included investments in equipment to facilitate tasks related to material handling and thereby reducing the amount of time spent on non-value adding activities. In addition, emphasis was put on information sharing and process improvement related to prototype production. Through a cost-effect matrix for evaluating improvements it was shown that Veoneer has the opportunity to proceed with the ‘low hanging fruit’ that requires low effort in relation to the benefits that can be drawn. In conclusion, the significant amount of time spent on ensuring material availability is reduced by the implementations made and together with the proposed suggestions, the information and material flow for prototypes can be improved.
Keywords: Produktion; Transport; Grundläggande vetenskaper; Hållbar utveckling; Övrig industriell teknik och ekonomi; Production; Transport; Basic Sciences; Sustainable Development; Other industrial engineering and economics